Isolation and Complete Genome Sequence Analysis of Kosakonia cowanii Pa82, a Novel Pathogen Causing Bacterial Wilt on Patchouli - Zhang, Yong; Wang, Bangwei; Li, Qiao; Huang, Derui; Zhang, Yuyao; Li, Guangwei; He, Hong (Frontiers in Microbiology, 2022)
Pogostemon cablin (patchouli), an important medicinal and aromatic plant, is widely used in traditional Chinese medicine as well as in perfume industry. Patchouli plants are susceptible to bacterial wilt disease, which causes significant economic losses by reduction in yield and quality of the plant products. However, few studies focus on the pathogens causing bacterial wilt on patchouli. In this study, strain Pa82 was isolated from diseased patchouli plants with typical bacterial wilt symptoms in Guangdong province, China, and was confirmed to be a highly virulent pathogen of patchouli bacterial wilt. Comparative sequence analysis of 16S rRNA gene showed that the strain was closely related to Kosakonia sp. CCTCC M2018092 (99.9% similarity) and Kosakonia cowanii Esp_Z (99.8% similarity). Moreover, phylogenetic tree based on 16S rRNA gene sequences showed that the strain was affiliated with genus Kosakonia. Further, the whole genome of strain Pa82 was sequenced, and the sequences were assembled and annotated. The complete genome of the strain consists of one chromosome and three plasmids. Average nucleotide identity and phylogenetic analysis revealed that the strain belongs to Kosakonia cowanii (designated Kosakonia cowanii Pa82). Virulence-related genes of the strain involved in adherence, biofilm formation, endotoxin and other virulence factors were predicted. Among them, vgrG gene that encodes one of the type VI secretion system components was functionally validated as a virulence factor in Kosakonia cowanii Pa82 through construction of Tn5 insertion mutants and identification of mutant defective in virulence.